2018
DOI: 10.1007/s00330-018-5518-8
|View full text |Cite
|
Sign up to set email alerts
|

Task-based quantification of image quality using a model observer in abdominal CT: a multicentre study

Abstract: ObjectiveWe investigated the variability in diagnostic information inherent in computed tomography (CT) images acquired at 68 different CT units, with the selected acquisition protocols aiming to answer the same clinical question.MethodsAn anthropomorphic abdominal phantom with two optional rings was scanned on 68 CT systems from 62 centres using the local clinical acquisition parameters of the portal venous phase for the detection of focal liver lesions. Low-contrast detectability (LCD) was assessed objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
(27 reference statements)
1
16
0
Order By: Relevance
“…In line with the findings of previous studies [ 45 52 ], we revealed appreciable differences in all CT image quality indices across scanners/acquisitions protocols. Noise level ( Table 4 ), peak position of NPS curve ( Table 5 ), f 50% ( Table 7 ), f 10% ( Table 7 ) and contrast threshold for a typical object size of 3 mm ( Fig 4 ) differed across scanners/acquisition protocols up to 62.8%, 42.8%, 35.7%, 23.8% and 56.7%, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with the findings of previous studies [ 45 52 ], we revealed appreciable differences in all CT image quality indices across scanners/acquisitions protocols. Noise level ( Table 4 ), peak position of NPS curve ( Table 5 ), f 50% ( Table 7 ), f 10% ( Table 7 ) and contrast threshold for a typical object size of 3 mm ( Fig 4 ) differed across scanners/acquisition protocols up to 62.8%, 42.8%, 35.7%, 23.8% and 56.7%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, a number of CT scanners with different models or by different manufacturers are often installed in a hospital centre and used by various departments. Previous phantom studies, mainly focused on body applications, have shown that CT image quality can vary substantially across scanners [ 45 48 ], even when similar acquisition protocols are employed [ 49 52 ]. For instance, in a multicentre study, Racine et al [ 45 ] have compared the image quality of 68 scanners, in terms of only low contrast detectability, using local clinical acquisition protocols for abdominal CT examinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantitatively evaluate image quality in the Digimouse, a channelized Hoteling observer [ 23 , 24 ] was used in the context of lesion detectability. The area under the curve (AUC) was used as a figure of merit.…”
Section: Resultsmentioning
confidence: 99%
“…Iterative reconstruction techniques have been introduced as one potential method for improving contrast‐to‐noise ratio while reducing radiation exposure in CT. However, for the assessment of CT performance with iterative reconstruction at reduced exposure, task‐based studies of image quality are preferred to studies measuring contrast‐to‐noise ratio and subjective assessments of image quality, 4 as noise equivalence and subjective imaging preference are not sufficient substitutes for diagnostic efficacy. Some examples of task‐based studies assessing CT performance at reduced exposure include those assessing the detection of renal calculi, 5–7 lung nodules, 8,9 and simulated low‐contrast low‐attenuation (LCLA) liver lesions 10,11 …”
Section: Introductionmentioning
confidence: 99%